PENTINGNYA PEMBUATAN LAPORAN KEUANGAN BAGI PELAKU USAHA UMKM DI KABUPATEN PEKALONGAN - ajeng nafilatun nikmah (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to determine the development of MSME businesses in recording financial reports, so that later they can be used as material for evaluating researchers to socialize recording and reporting of financial reports for MSME business actors. In this study using the literature review method obtained from previous research books and journals related to Making Financial Reports for MSME Business Actors and using a technique in the form of the documentation method. Based on this study, information was obtained that MSME actors often underestimate the recording of financial reports, even considering that financial reports are something complicated. Padalah by recording financial reports according to SAK EMKM standards can increase the credibility of the company and can be used as material for evaluating the company. So far, MSME entrepreneurs only make very simple financial reports, so they are not in accordance with SAK EMKM rules. This is triggered by several factors, namely the lack of human resources due to lack of knowledge and education, lack of capital, weak business networks and the ability to penetrate small businesses, lack of facilities and infrastructure, and business climate. Making financial reports actually has many benefits for MSME businesses, such as when a company needs capital assistance from an external party, the existence of financial reports can be used as a reference and benchmark for external parties when they want to lend money to the company.